Single‐center study to determine the safety and efficacy of CT‐707 in Chinese patients with advanced anaplastic lymphoma kinase‐rearranged non‐small‐cell lung cancer - Song, Peng (Thorac Cancer, 2020)
INTRODUCTION: It has been proven that ALK‐rearranged non‐small cell lung cancer (NSCLC) is sensitive to ALK inhibitors while the chemotherapy resistance is unavoidable. In this study, safety and antitumor activity of the novel ALK inhibitor (ALKi) CT‐707 were evaluated in Chinese patients with advanced ALK‐rearranged NSCLC. METHODS: This single‐center, open‐label phase I study recruited adult patients with ALK‐rearrangement (confirmed by fluorescence in situ hybridization and/or immunohistochemistry) of locally advanced/metastatic malignancies including NSCLC. This study consisted of two parts: dose escalation and dose expansion. CT‐707 was administered orally once a day for 21 days. RESULTS: A total of 13 patients who were treated with CT‐707 from 450 to 600 mg (in the dose increasing phase) were enrolled in this trial (two patients were previously treated with crizotinib). There were 12 patients diagnosed with lung adenocarcinoma and one patient with malignant pleural mesothelioma. After treatment, grade 3 diarrhea (600 mg once a day) was found as dose‐limiting toxicity (DLT).The most common adverse events included diarrhea (92%), elevated aspartate aminotransferase (61%), elevated alanine aminotransferase (54%), hair loss (38%), and vomiting (31%). The overall response rate was 77% (10/13). Among all patients, four of the five patients who did not receive any treatment, one of the two patients who had received treatments with crizotinib, and five of the six patients who received standard chemotherapy achieved partial response (PR). One patient reached a complete remission (CR). CONCLUSIONS: This study indicated that CT‐707 is clinically effective as a new antitumor drug for Chinese lung adenocarcinoma patients with ALK rearrangement. It is safe and reliable and the dose‐expansion phase recruitment has started.